2016
DOI: 10.5194/amt-9-491-2016
|View full text |Cite
|
Sign up to set email alerts
|

EARLINET Single Calculus Chain – technical – Part 1: Pre-processing of raw lidar data

Abstract: Abstract. In this paper we describe an automatic tool for the pre-processing of aerosol lidar data called ELPP (EAR-LINET Lidar Pre-Processor). It is one of two calculus modules of the EARLINET Single Calculus Chain (SCC), the automatic tool for the analysis of EARLINET data. ELPP is an open source module that executes instrumental corrections and data handling of the raw lidar signals, making the lidar data ready to be processed by the optical retrieval algorithms. According to the specific lidar configuratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 32 publications
1
43
0
2
Order By: Relevance
“…The Gobabeb site, in the Namib Desert, is far less sensitive to the effect of urban pollution than the Durban and Pretoria sites. It can be observed that all of these African sites exhibit an increase in the AOD values during the austral spring season, which is well known to be the biomass burning season (Eck et al, 2003;Garstang et al, 1996;Das et al, 2015;Piketh et al, 1999;Kumar et al, 2017). The daily AOD measurements performed between 15 April and 1 December 2015 were compared with background values in order to highlight the passage of the volcanic plume.…”
Section: Methodsologymentioning
confidence: 99%
“…The Gobabeb site, in the Namib Desert, is far less sensitive to the effect of urban pollution than the Durban and Pretoria sites. It can be observed that all of these African sites exhibit an increase in the AOD values during the austral spring season, which is well known to be the biomass burning season (Eck et al, 2003;Garstang et al, 1996;Das et al, 2015;Piketh et al, 1999;Kumar et al, 2017). The daily AOD measurements performed between 15 April and 1 December 2015 were compared with background values in order to highlight the passage of the volcanic plume.…”
Section: Methodsologymentioning
confidence: 99%
“…Another process leading to a cross adiabatic movement (by diabatic heating) is related to the so-called self-lifting effect (Boers et al, 2010;Siddaway and Petelina, 2011;de Laat et al, 2012). Absorption of shortwave solar radiation heats the smoke layers and creates buoyancy that can then result in an ascent of the aerosol layer over several kilometers altitude within 1-2 d (Siddaway and Petelina, 2011;de Laat et al, 2012). Such a heating is seasonally dependent.…”
Section: Self-lifting By Absorption Of Solar Radiationmentioning
confidence: 99%
“…They had a nonspherical shape after 7-10 d of travel towards Europe Hu et al, 2019) and even after months as will be shown here. Self-lifting effects caused by sunlight absorption and warming of the ambient air (Boers et al, 2010;Siddaway and Petelina, 2011;de Laat et al, 2012) then led to a further significant ascent of the soot-containing layers. The aerosol optical thickness (AOT) in the UTLS region must have exceeded values of 2-3 at 500 nm wavelength so that strong absorption in the visible spectrum and warming of the smoke layers occurred and enabled the fire smoke plumes to ascend by about 2-3 km d −1 during the first days after injection, as was observed with the spaceborne lidar aboard CALIPSO (Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation) (Khaykin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In particuar, low resolution (in both time and space) uncalibrated pre-processed products provided by the SCC EARLINET Lidar Pre-processor (ELPP) module (D'Amico et al, 2016) and aerosol optical properties vertical profiles provided by the SCC EARLINET Lidar data Analyzer (ELDA) module (Mattis et al, 2016) are made available. Recently a new version of the SCC has been released providing also standardized high-resolution pre-processed lidar products.…”
Section: Earlinetmentioning
confidence: 99%
“…During the last years, EARLINET has increased strongly its observing capacity with the addition of new stations and system upgrade, namely, the installation of depolarization channels. Besides, the further development of the Single Calculus Chain (D'Amico et al, 2015(D'Amico et al, , 2016Mattis et al, 2016) under the ACTRIS (Aerosol, Clouds and Trace gases Research InfraStructure Network) umbrella eliminated the inconsistencies in the retrieval procedures and in the signal error calculation, and automated the data evaluation, and now allows for the NRT data processing and the generation of tailored products network-wide. EAR-LINET has already demonstrated the networks' NRT capabilities as well as assisted modelling studies in NRT evaluation and 2 https://doi.org/10.5194/acp-2020-178 Preprint.…”
Section: Introductionmentioning
confidence: 99%